Avaliação ultramorfológica de formas imaturas e adultas de Lutzomyia lonpipalpis Lutz e Neiva, 1912 (Diptera: Psichodidae) procedentes do campo e de colônias de laboratório - VALENÇA, Luiz Augusto França (2015)
Lutzomyia longipalpis has a great importance in public health to be transmitter of visceral leishmaniasis in the New World. This study aimed to observe, with the aid of scanning electron microscopy, the morphological and ultrastructural relevant aspects of the immature forms (eggs and larvae and pupae) and the laboratory adults species of L. longipalpis, comparing those from the field with those from laboratory colony. Eggs exochorion observations showed that the species L. longipalpis has unconnected crest ornaments and the presence of tubercles along its entire surface. In general, all larval stages of this species are similar. However, both morphological characteristics as distinct ultrastructural were observed. Morphology: size of the larvae in the different stages of growth had wormlike form, translucent white color, small and delicate caudal bristles developing along the larval growth, detailing the front wall of the first-stage larva, caudal segments. Ultrastructural characteristics as pseudo-feet, jaw, trichodea bristles, filiform bristles were observed. We can see in the larval exuvia pupae, body segments, forming the wings, antennae and legs. Regarding the analysis of adults both from field as those from colony in the laboratory, we can observe their morphological characteristics of male and female genitalia and sensilla. About the ultrastructural observations were seen: forms and distribution of setae and spines along the vector of the body, besides the sensilla escamiformes, trichodea and capamiformes. This study may provide a new basis for the taxonomy of this important vector in the search for more information in order to promote better knowledge about the biology and adaptability in regions with different soil and climatic characteristics.